Использование треморометра для оценки функционального состояния человека - Демченко, М. В. (ХНУРЕ, 2018)
In this article, there is a device that allows you to assess the functional state of muscle tremor. Studies are carried out using devices - a tremorometer. Assesses the degree of fatigue and fitness of a person to perform his professional duties. The article describes the structure and use of the tremorometer. The use of the device before and after performing any work allows one to judge the change in the functional state of the subject.
Keywords: треморометр; оценка состояния человека; персональный компьютер